Analysis of Calculations And Reporting of Annual Corporate Income Tax At PT. Interconterminal Indonesia Year 2020 - Aris Munandar; Aliyeva Patimat Shapiulayevna; Harsi Romli (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
The calculation and reporting of the Annual Corporate Income Tax Return is a tax obligation that must be fulfilled by corporate taxpayers no later than the fourth month at the end of the tax period. This study aims to analyse whether the calculation and reporting of the Annual Corporate Income Tax Return that has been carried out by PT. Intercon Terminal Indonesia complies with Law Number 36 of 2008 concerning the Fourth Amendment to Law Number 7 of 1983 concerning Income Tax and Regulation of the Director General of Taxes Number PER-19/PJ/2014 concerning the Second Amendment to Regulation of the Director General of Taxes Number Per-34/Pj/2010 Concerning the Forms of Annual Income Tax Returns for Individual Taxpayers and Corporate Taxpayers Along with Instructions for Filling In. The results of the study conclude that in calculating and reporting the Annual Corporate Income Tax Return PT. Intercon Terminal Indonesia has not fully complied with the Income Tax Law and Director General of Tax Regulations. So that in 2020, the company should have recorded a loss of Rp. 3,308,457,027 and overpaid tax of Rp. 437,556,885.